Online measurement of piston-assembly friction with wireless IMEP method under fired conditions and comparison with numerical analysis. (April 2021) - Wen, Chengwei; Meng, Xianghui; Xie, Youbai; Liu, Ruichao; Kong, Xiaoli; Li, Rui; Liu, Zhan; Fang, Congcong
Highlights: Measurement of piston-assembly friction under fired conditions is implemented. The wireless IMEP method is applied to obtain the piston-assembly friction. A measurement system is modified to meet the demands of an online test. The lubrication and dynamic models are built for piston rings and piston skirt. The measured results are compared with the numerical simulations. Abstract: Reliable and accurate measurement of piston-assembly friction is urgently required in the field of internal combustion engines. With few modifications to the engine, an improved wireless instantaneous indicated mean effective pressure (IMEP) technique for measuring piston-assembly friction under fired conditions is first presented in this paper. The piston-assembly friction is obtained indirectly by measuring the cylinder pressure, the connecting rod force, the crank position and the engine speed under various conditions. A measurement system, mainly including a wireless rechargeable telemetry module, a data acquisition system and three typical sensors, is modified for an online test. After the in-situ measurement and the simulations, it is found that the simulation results generally coincide with the measured data. Though the current measurement technique still suffers from challenges in signal synchronization, noise control and system reliability, it can be applied for the direct performance evaluation of piston assembly in the future.